Gypsy boy one boy's struggle to escape from a secret world - Walsh, Mikey (London Hodder Paperbacks, 2010)
Gypsy boy is the first commercial memoir written by someone on the inside of the notoriously secretive culture of the Romany Gypsies.
Originally published: London: Hodder & Stoughton, 2009.
First published in paperback in 2010.
UCWS-3352g donated by Adrienne Maguddayao - May 2018
Keywords: Romanies -- Great Britain -- Biography; Romanies -- Social life and customs